PROBLEMATIKA TAFSIR FEMINIS: Studi Kritis Konsep Kesetaraan Gender - Husaini, Adian; Husni, Rahmatul (IAIN Ponorogo, 2015)
Abstract: Gender equality is a discourse that is still warm to be discussed by Muslim feminists. Initiators and supporters of gender equality often questioned about Islamic laws that were considered to be unfair since they had positioned men and women differently such as the obligotary forÂ adhan (call for prayer), the Friday prayers, the number of goats in aqiqah (welcoming celebretion of childâ€™s birth), and the compulsory of breastfeeding and caring for the child. Through content analysis, this study tried not only to elaborate a number of products of reintepretation based on Qur'anic Hermeneutics version of the female models but also show the history of the ideology of feminism and the inappropriateness of using hermeneutical exegesis. Feminism departed from the ideology of hatred as a form of resistance against the oppression of women that occurred in Western Christian civilization in th past. Hermeneutical exegesis approach also came from an academic Christian tradition that considered Bible text not as a Godâ€™s revelation. Both conditions were diametrically opposed to the fact in the Islamic tradition. The text of the Qurâ€™an in Islam, was not a cultural product, but as a revelation of God to human being in the world. Historically,Â Islam never surpressed to women, but it placed women in a glorious position. Meanwhile, different roles given to men and women were aimed at getting maximum benefits to the world so that they could work together and complement each other to achieve happiness in the world and the hereafter.Ø§Ù„Ù…Ù„Ø®Øµ :Ø£ØµØ¨Ø Ù…ÙˆØ¶ÙˆØ¹ Ø§Ù„Ù…Ø³Ø§ÙˆØ§Ø© Ø¨ÙŠÙ† Ø§Ù„Ø±Ø¬Ù„ ÙˆØ§Ù„Ù…Ø±Ø£Ø© Ù…ÙˆØ¶ÙˆØ¹ ØØ¯ÙŠØ« ØØ§Ø±Ù‘ Ø¨ÙŠÙ† Ù†Ø³Ø§Ø¡ Ø§Ù„Ù†Ø³ÙˆÙŠØ© Ø§Ù„Ù…Ø³Ù„Ù…Ø§Øª. Ù‚Ø¯ ØªØªØ³Ø§Ø¦Ù„ Ù…Ø¤Ø³Ù‘ÙØ³Ø§Øª Ø§Ù„Ù…Ø°Ù‡Ø¨ Ø§Ù„Ù†Ø³ÙˆÙŠ ÙˆÙ…Ø¤ÙŠÙ‘Ø¯ÙˆÙ‡Ø§ Ø§Ù„Ø´Ø±ÙŠØ¹Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØªÙŠ â€“ ÙÙŠ Ù†Ø¸Ø±Ù‡Ù† â€“ Ù„Ù… ØªÙƒÙ† Ø¹Ø§Ø¯Ù„Ø© ÙˆØªØ¶Ø¹ Ø§Ù„Ø±Ø¬Ù„ ÙˆØ§Ù„Ù…Ø±Ø£Ø© ÙÙŠ Ù…Ø³ØªÙˆÙ‰ ÙˆÙ…ÙƒØ§Ù† ØºÙŠØ± Ù…ØªÙˆØ§Ø² ØŒ Ù…Ø«Ù„ Ù…Ø´Ø±ÙˆØ¹ÙŠØ© Ø§Ù„Ø£Ø°Ø§Ù† ÙˆØ£Ø¯Ø§Ø¡ ØµÙ„Ø§Ø© Ø§Ù„Ø¬Ù…Ø¹Ø© Ù„Ù„Ø±Ø¬Ø§Ù„ ÙˆØ¹Ø¯Ø¯ Ø§Ù„ØºÙ†Ù… ÙÙŠ Ø§Ù„Ø¹Ù‚ÙŠÙ‚Ø© Ù…Ø®ØªÙ„Ù Ø¨ÙŠÙ†Ù‡Ù…Ø§ØŒ ÙˆØªÙƒÙ„ÙŠÙ ØØ¶Ø§Ù†Ø© Ø§Ù„Ø£ÙˆÙ„Ø§Ø¯ ÙˆØ±Ø¹Ø§ÙŠØªÙ‡Ù… Ø¹Ù„Ù‰ Ø§Ù„Ù†Ø³Ø§Ø¡. ØØ§ÙˆÙ„Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© â€“ Ø¹Ù† Ø·Ø±ÙŠÙ‚ ØªØÙ„ÙŠÙ„ Ø§Ù„Ù…Ø¶Ù…ÙˆÙ† Ù„ÙŠØ³ ÙÙ‚Ø· Ø¯Ø±Ø§Ø³Ø© Ù†ØªØ§Ø¦Ø¬ Ù…Ù† Ø¥Ø¹Ø§Ø¯Ø© ØªÙØ³ÙŠØ± Ø§Ù„Ù‚Ø±Ø¢Ù† Ø¨Ù†Ù…Ø· Ø§Ù„Ù‡Ø±Ù…ÙŠÙ†ÙŠØ·ÙŠÙ‚Ø§ Ù„Ø¯Ù‰ Ø§Ù„Ù†Ø³Ø§Ø¡ Ø¨Ù„ Ø¹Ø±Ø¶Øª ÙƒØ°Ù„Ùƒ ØªØ§Ø±ÙŠØ® Ø¥ÙŠØ¯ÙŠÙˆÙ„ÙˆØ¬ÙŠØ© Ø§Ù„Ù†Ø³ÙˆÙŠØ© ÙˆØ¹Ø¯Ù… ØµØØ© Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ù‡Ø±Ù…ÙŠÙ†ÙŠØ·Ù‚ÙŠ ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¬Ø§Ù„. Ø§Ø¹ØªÙ…Ø¯Øª Ø§Ù„Ù†Ø³ÙˆÙŠØ© Ø¹Ù„Ù‰ Ø¥ÙŠØ¯ÙŠÙˆÙ„ÙˆØ¬ÙŠØ© Ø§Ù„ÙƒØ±Ù‡ ÙˆØ§Ù„ØÙ‚Ø¯ ÙƒØ´ÙƒÙ„ Ù…Ø¹Ø§Ø±Ø¶Ø§Øª Ø¹Ù„Ù‰ Ø£Ù†ÙˆØ§Ø¹ Ø§Ù„Ø¸Ù„Ù… ØªØ¬Ø§Ù‡ Ø§Ù„Ù…Ø±Ø£Ø© ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„ØºØ±Ø¨ÙŠ Ø§Ù„Ù…Ø³ÙŠØÙŠ ÙÙŠ Ø§Ù„Ù‚Ø±ÙˆÙ† Ø§Ù„Ù…Ø§Ø¶ÙŠØ©. ÙˆØ£ØµÙ„ Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ù‡Ø±Ù…ÙŠÙ†ÙŠØ·Ù‚ÙŠÂ ÙƒØ°Ù„Ùƒ Ù…Ù† Ø§Ù„ØªÙ‚Ø§Ù„ÙŠØ¯ Ø§Ù„Ø£ÙƒØ§Ø¯ÙŠÙ…ÙŠØ© Ø§Ù„Ù…Ø³ÙŠØÙŠØ© Ø§Ù„Ù…Ø¹ØªØ¨Ø±Ø© Ø£Ù† Ø§Ù„Ø¥Ù†Ø¬ÙŠÙ„ Ù„ÙŠØ³ ÙˆØÙŠØ§ ÙŠÙˆØÙŠ. Ù‡Ø°Ø§Ù† Ø§Ù„Ø´ÙŠØ¦Ø§Ù† Ù…ØªÙ†Ø§Ù‚Ø¶Ø§Ù† Ø¨Ù…Ø§ ÙÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ù…Ù† Ø£Ù† Ø§Ù„Ù‚Ø±Ø¢Ù† Ù„ÙŠØ³ Ø§Ù†ØªØ§Ø¬Ø§ Ø«Ù‚Ø§ÙÙŠØ§ Ø¨Ù„ ÙˆØÙŠ Ù…Ù† Ø§Ù„Ù„Ù‡. Ù„ÙŠØ³ ÙÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø§Ù„ØªØ§Ø±ÙŠØ® Ø¹Ù† Ø¸Ù„Ù… Ø§Ù„Ø±Ø£Ø© Ø¨Ù„ Ù‡Ùˆ ÙˆØ¶Ø¹Ù‡Ø§ ÙÙŠ Ù…Ø±ØªØ¨Ø© Ø±ÙÙŠØ¹Ø©. Ø£Ù… ØªÙØ±ÙŠÙ‚ Ø§Ù„Ø¯ÙˆØ± Ø¨ÙŠÙ†Ù‡Ù…Ø§ Ù„ÙŠØ³ Ø¥Ù„Ø§ Ù„ÙŠÙƒÙˆÙ† ÙƒÙ„ Ù…Ù†Ù‡Ù…Ø§ Ù†Ø§ÙØ¹Ø§ ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ù†ÙŠØ§ ÙˆÙŠØªØ¹Ø§ÙˆÙ†Ø§Ù† ÙˆÙŠØªÙƒØ§Ù…Ù„Ø§Ù† Ù„Ù„ØØµÙˆÙ„ Ø¹Ù„Ù‰ Ø§Ù„Ø³Ø¹Ø§Ø¯ØªÙŠÙ† ÙÙŠ Ø§Ù„Ø¯Ù†ÙŠØ§ ÙˆØ§Ù„Ø¢Ø®Ø±Ø©.Abstrak: Kesetaraan gender merupakan diskursus yang tetap hangat diperbincangkan para feminis muslim. Penggagas dan pendukung kesetaraan gender tidak jarang mempersoalkan hukum Islam yang dianggap kurang adil dan memposisikan laki-laki dan perempuan secara berbeda seperti pembebanan adzan, shalat Jumâ€™at, jumlah kambing saat aqi>qah di satu sisi, dan pembebanan menyusui dan merawat anak di sisi yang lain. Melalui content analysis kajian ini mencoba tidak saja untuk mengelaborasi sejumlah produk reintepretasi al-Qurâ€™an model Hermeneutika versi kaum perempuan tetapi juga menunjukkan sejarah ideologi feminisme serta ketidaktepatan penggunaan tafsir hermeneutika. Feminisme berangkat dari ideologi kebencian sebagai bentuk perlawanan terhadap penindasan perempuan yang terjadi dalam peradaban Barat-Kristen di masa lalu. Metode tafsir Hermeneutika juga berasal dari tradisi akademis Kristen yang menganggap teks Bible bukan sebagai wahyu. Kedua kondisi ini berseberangan secara diametral dengan fakta dalam tradisi Islam. Teks al-Qurâ€™an, dalam Islam, bukanlah produk budaya, melainkan wahyu. Islam tidak memiliki sejarah penindasan terhadap kaum perempuan, bahkan memposisikan perempuan dalam posisi yang mulia. Perbedaan peran yang diberikan kepada laki-laki dan perempuan ditujukan agar keduanya dapat bermanfaat secara maksimal di dunia, untuk saling bekerja sama dan melengkapi demi mencapai kebahagiaan dunia dan akhirat.Keywords: kesetaraan, gender, perempuan, feminisme, tafsir, hermeneutik.